Обґрунтування розроблення та реалізації проекту вивчення курсу українознавства за вибором «Я люблю Україну» для 2-4 класів загальноосвітніх навчальних закладів - Чабайовська, Марія; Chabayovska, Maria (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто питання актуальності створення проекту вивчення курсу українознавства за вибором «Я люблю Україну»для 2-4 класів загальноосвітніх навчальних закладів; визначено об’єкт, предмет, гіпотезу, мету та завдання дослідження; вказана наукова новизна, практична значущість, вірогідність результатів експерименту, його теоретико-методологічна основа; обґрунтовано компетентності, що формуватимуться в процесі вивчення даного курсу; розкрито його змістове наповнення. The article covers the issue of the need for creation of the project of choise course of Ukrainian Studies “I love Ukraine” for classes 2-4 of regular educational institutions; there are determined object, content, gypothesis, aim, and tasks of the research; there is indicated scientific innovation, practical importance, possible results of the experement, its theoretic and methodological basis; there are analised key(inter-disciplinary) – social, civic, communication, skill tolearn and objective – socio-cultural competency, which will be form edin the process of study of the given course; its content is presented. There is foreseen integration of content with such courses as Ukrainian language, Literature Reading, History, Christian Ethics, Arts, Natural Sciences, Music Studies, etc... Important role plays country study and linguistic studies. Information on state and calender folk holidays is provided on seasonal basis. It is recommended to use follow in effective forms of lessons and activities – project (mini-project), liguistic-literature holiday, morning performance, excursion, lesson of brave behaviour, meeting famous people, situationally role playing game, topic oriented role playing game, game-dramatization, insinuation, game-communication, game-trip, playing exercise, collective art drawing, communication, the magic notebook, verbal journal, design of album, imaginary trip, contest, game, school of ethics, demonstration, storytelling, modeling, quiz, exibition of drawings, operation-raid, exibition-messe, exchange of messages, charitable action, minutes with arts, hour of observation, hour of adoration, theater perfomance, recording class diary, cossack games, merry competitions, relay race, puppies theater, pet scare and flora care, etc. It is indicated that course content can be used for external educational activities (conduction of hour of communication and etc..).
Analysis of development and implementation of choice course project of ukrainian studies “I love Ukraine” for 2nd-4th classes of elementary schools
Keywords: національно-патріотичне виховання; «Стратегія національно-патріотичного виховання дітей та молоді на 2016-2020 роки»; «Концепція національно-патріотичного виховання дітей та молоді»; national-patriotic education; “Strategy of national-patriotic education of chieldren and youth for 2016-2020”; “Concept of national-patriotic education of chieldren and youth”